Model of Implementation of Information Technologies in the Training of Future Specialists in Higher Education Institutions - Kabak, Vitalii; Tulashvili, Yurii; Horbatiuk, Roman (Educological discourse, 2025)
The article, based on the analysis of domestic and foreign scientific research, reveals conceptual approaches to modeling the process of professional training of educational applicants with an emphasis on ensuring the formation of their readiness for effective professional activity. On the basis of a comprehensive analysis of educational and professional programs and the content of training for students majoring in A5.39 Vocational Education (Digital Technologies) and A4.09 Secondary Education (Computer Science), generalized requirements for their professional training in a higher education institution are identified. Within the framework of the study, the author’s model has been developed, which includes a combination of conceptual and target, organizational and content, procedural and activity, and criterion and evaluation blocks that ensure the comprehensive formation of future teachers’ readiness for the effective use of information technology. The basis of the projected model is the organizational and pedagogical conditions for the training of an educational specialist, determined by expert evaluation, which combine the motivational component and the introduction of modern information technologies in the process of their training, a favorable information environment to ensure the development of their search and creative abilities in the process of self-education, as well as the component of increasing the competence of teachers who teach special technical disciplines in the process of improving their own pedagogical skills. The model takes into account modern information technology tools that contribute to the formation of professional competencies of a future specialist in the field of education (hardware, software, software development tools). The result of the implementation of the author’s model is the readiness of future specialists in the educational sphere (at high and sufficient levels) to use (and professional application of) information technology tools in their future professional activities. The proposed model is an effective tool for improving the content and organization of training of competitive specialists in the field of education in the context of digital transformation of education.